The determinants of angioedema attacks related to dental and gingival procedures in hereditary angioedema patients - Nihal M. Gokmen; Reyhan Gumusburun; Asuman Camyar; Semiha Ozgul; Melih Ozısık; Tugba Turk; Aytul Z. Sin (BMC Oral Health)
Abstract Background The factors causing acute attacks during dental and gingival procedures in patients with hereditary angioedema due to C1 inhibitor (HAE-C1INH) deficiency remain unclear. Our aim is to investigate the patients and dental/gingival procedure characteristics influencing acute attack risk. Methods A retrospective review of 638 dental interventions in 40 HAE-C1INH patients was conducted between June and September 2023 using questionnaires, diaries, and medical charts. Data included demographics, clinical details, intervention history, and types of procedures, aiming to understand acute attack patterns. Results A total of 40 HAE-C1INH patients (36 type 1; 23 female; median age 41.5 (30.8–53.5) years; median disease onset age 10.5 (5.0–15.0) years; median annual attack frequency 24.5 (12.0–52.0) were analyzed. Facial and laryngeal edema history were found in 82.5% and 67.5% of patients, respectively. Treatment-naive median serum C4 level, C1 inhibitor (C1INH) function and C1INH antigenic level (for type 1 HAE) were 6 mg/dL (IQR: 5–6; normal range: 10–40 mg/dL), 13.2% (IQR: 7.2–18.8; normal range: 70–130%), and 5.6 mg/dL (IQR: 3–7; normal range: 0.21–0.39 g/L), respectively. Acute angioedema attacks were observed in 72 out of 638 procedures. Before HAE-C1INH diagnosis, per-person attack frequency and per-procedure attack frequency were found to be 26.5% (9/34), and 15.74% (95% CI:12.28–19.71), respectively. Higher annual attack frequency (p = 0.038), lower C1INH function (p = 0.044), and female gender (p = 0.047) related to acute attacks due to dental interventions in pre-diagnosis period. Prophylactic HAE treatment significantly reduced the frequency of acute attacks following dental procedures. The attack frequency per procedure was 14.6% (95% CI: 11.48–18.20) among untreated patients and 3.23% (95% CI: 1.19–6.89) among those receiving prophylactic medication, post-diagnosis. Tooth extraction, wisdom teeth extraction and challenging surgical tooth extraction were found to be more risky. Conclusion Prophylactic HAE treatment significantly reduced the frequency of acute attacks, compared to the untreated group. Pre-procedural prophylactic treatment is particularly important for safer dental care in HAE patients with higher annual attack frequency, lower C1INH function, and female gender, especially during high-risk procedures such as tooth extraction, wisdom teeth extraction, and challenging surgical tooth extractions.